PERAN PENDIDIKAN KEWIRAUSAHAAN DALAM MENUMBUHKAN MINAT WIRAUSAHA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS BHINNEKA PGRI - Arum, Rovita; Anasrulloh, Muhammad (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
This study aims to find out the role of entrepreneurship education, the implementation of entrepreneurship education, and find out the factors that can affect entrepreneurial interest in students. This study uses a descriptive qualitative approach. The data sources in this study are the heads of ormawa, career, entrepreneurship, students and alumnus of Universitas Bhinneka PGRI, entrepreneurial lecturers, and students of the 8th semester of the 2023/2024 academic year. The data collection method is by observation, documentation, and interview methods. Meanwhile, the data analysis method uses the data triangulation system to test the validity of the data that has been obtained. The data obtained is from observations, interviews, and documentation that are reduced or processed to obtain valid conclusions. The results of this study show that; 1. Entrepreneurship education carried out at Universitas Bhinneka PGRI directly and indirectly as a step for universities to equip their students in growing and developing interest in entrepreneurship, 2. The implementation of entrepreneurship education learning activities does not only emphasize material and theory but there is applied training by going directly into the field, 3. Students' interest in entrepreneurship is influenced by several factors, including entrepreneurial education factors, environmental factors, family factors, relationship factors, expectation factors, and capital factors.